DETERMINING ISOSBESTIC POINT AND DETERMINATION OF P-NITROFENOL COMPOUND by SPEKTROFOTOMETRI - Heru Pratomo (Jurnal Penelitian Saintek, 2003)
The determined of isosbestic point from weak acids or weak bases areusually important for  indicator solutions. The indicators that used in acid-base titration have pH exactly, and this is usefulfor determine the end of titration. The aims of this research are  (1)  to determine ofwavelength on isosbestic point of p-nitro phenol, and (2) to determine of dissociation constant of p-nitro phenol. The determined of isosbestic has  done  with  spectrophotometric  method,  to  the  p-nitro  phenol solutions in several pH, at region of wavelength between 280 nm - 450 nm. In this research, indicate that the isosbestic point ofp-nitro phenol at the wavelength of 348 nm, and pH about 6.7. From this research also can be determined that the dissociation constant (KaYof p-nitro phenol is 6.48 x 10-8,not too different compared with K, literature, is7.08 x 10-8.